Why Women Also Know History - Prifogle, Emily; Wulf, Karin (Journal of women's history, 2020)
In the last two decades, women have earned 42 percent of all history PhDs and, according to recently collected data from the American Historical Association (AHA), women have achieved near parity in academic hiring.2 Yet women are underrepresented in citation counts, publishing, hiring, promotion, peer review, grant awards, syllabi, and conference panels—nearly every measure of an academic historian's professional life.3 While recognizing parity in hiring, the AHA simultaneously noted that gender plays an additional "role in the professional experiences of women" in the form of "compensation, tenure decisions, sexual harassment, parental leave policies, and more subtle forms of discrimination [that have] held back women historians for years. [...]hashtags have proven effective in creating collective syllabi like the #Charleston-Syllabus created by Keisha Blain, Chad Williams, and Kidada Williams in response to the shooting in South Carolina during a Bible study meeting at the Emanuel African Methodist Episcopal Church in 2015.6 Crowdsourced syllabi draw together more than a reading list for critical engagement on a particular subject; they also use a hashtag to create and mobilize inclusive communities. [...]not unrelated, we are increasing our collaboration with other organizations and initiatives. [...]we are thinking hard about how to get into journalists' workflows, and we are not alone.